Drosophila morgue associates with SkpA and polyubiquitin in vivo. - Ying Zhou; Yiqin Wang; Barbara A Schreader; John R Nambu (PLoS ONE, 2013)
Morgue is a unique ubiquitination protein that influences programmed cell death and circadian rhythms in Drosophila. We have found that over-expression of wild-type Morgue results in organismal lethality. This over-expression phenotype was used as the basis for an in vivo functional assay to investigate the importance of the Morgue zinc finger, F box, Ubiquitin E2 Conjugase Variant (UEV) domain, and active site Glycine residue. Removal of the zinc finger or UEV domain reduced Morgue's ability to induce lethality and enhance cell death. In contrast, lack of the F box as well as several different substitutions of the active site Glycine did not alter Morgue-induced lethality or cell death enhancement. To further characterize Morgue functions, a Flag:Morgue protein was used to isolate Morgue-associated proteins from whole adult Drosophila. Mass spectrometry analysis of the Morgue-associated proteins identified SkpA as well as a ubiquitin multimer. The identification of SkpA is consistent with previous in vitro studies and further suggests Morgue acts in an SCF-type ubiquitin E3 ligase complex. The identification of poly-ubiquitin was unexpected and this interaction had not been previously identified. The associated poly-ubiquitin was found to exhibit a Lys-48 topology, consistent with distinct functions of Morgue in proteasome-mediated protein turnover. Multiple regions of Morgue were subsequently shown to be required for poly-ubiquitin binding. Overall, Morgue is a novel multi-functional ubiquitin-binding protein.